CONSTRUÇÃO DE UM LABORATÓRIO COMPACTO PARA REAÇÕES ORGÂNICAS SUSTENTADO POR ENERGIA SOLAR - Kuchla, Mauricio (2016)
Compact equipment for synthesis and distillation of essences applied for teaching chemistry. It’s well known that public schools face many problems, both with regard to infrastructure as well as the difficulty in finding an efficient process of teaching and learning. In order to try to improve this situation, it was built a chemical portable equipment to develop experiments, especially in organic chemistry, which can serve as an alternative tool to arouse the interest of students in this discipline. This small device was built to show reflow reactions and distillations. Other important characteristics of the device are: reduced dimensions 13cm x 55,5cm x 60,5cm weighing 20kg, energy self-sufficient by having solar battery charging source through a set of solar cells attached to the system, has lighting, closed cooling system and can be used in the classroom or outside it. Used mainly for synthesis and distillation of flavorings and extraction of natural essences. This equipment can also be used for interdisciplinary studies involving physics and electronics. The most important aspect of this proposal is precisely to use experimentation and technology in favor of the learning processes in chemistry, taking environmental care, supporting expositive classes, so that they become more meaningful to students. The project presents an experimental alternative to public schools, where investments are low, and schools that do not have laboratories or equipment to perform simple experiments. The system was used in the teaching content of esters, for third classes of high school in Prudentópolis town through a series of 10 lessons, starting with research making use of available technology in schools (computer, phone and tablet), for subsequent application in experimental activities using the equipment proposed in this work. At the end, the obvious enthusiasm that the students had when working with practical classes has been observed. In conclusion, this equipment has an excellent cost benefits for public schools, where investments, especially in laboratories and equipment, are very low. Keywords: Chemistry Education, Organic Reactions, essential oils.